An improved fish swarm algorithm to assign tasks and cut down on latency in cloud computing - Raed Abdulkareem Hasan; Royida A. Ibrahem Alhayali; Mostafa Abdulghafoor Mohammed; Tole Sutikno (Universitas Ahmad Dahlan, 2022)
Various researches have been conducted to discover the machinery that led to the evolvement of non-symmetric formation of groups by uncountable marine animals. The huge of tasks comes per unit of time brought obstacles to assign each to particular server, while task assignment have needed a fast strategy to make decision. Artificial fish affect the environment through their behavior and the behavior of their peers. Creating a synthetic fish model has two parts: variables and functions which could be used for task assignment. This paper present improved fish swarm algorithm (IFSA) for task assignment to reduce the latency in cloud computing that could achieve one green computing goals. The research trying to reduce the pending job numbers compared with exist research.